Use of segmental lengths for the assessment of growth in children with cerebral palsy - Bell, K.; Davies, P.; Boyd, Roslyn; Stevenson, R. (2012)
© Springer Science+Business Media, LLC 2012. All rights reserved. Measurement of height or recumbent length is essential for the assessment of linear growth in children. Children with cerebral palsy (CP) often grow poorly and assessment of growth in this population is further complicated by two main difficulties. Firstly, children may have joint contractures, muscular weakness, scoliosis, and/or involuntary movements that make standing or lying straight difficult, if not impossible. Hence, accurate and reliable measures of height or recumbent length are not always attainable in this population. Secondly, as a result of atypical growth patterns, generally accepted reference charts for typically developing children may not be appropriate for use in children with CP. Due to these difficulties segmental lengths such as knee height, tibial length or upper arm length are frequently used as alternatives. These measures are all reliable and valid alternative measures for height in children with CP. They have been recommended for inclusion in the routine growth assessment of this group when accurate or reliable direct measurements of height or recumbent length are difficult or not possible (Spender et al. 1989; White and Ekvall 1993; Chumlea 1994; Stevenson 1995; Gauld et al. 2004). Segmental lengths can be compared directly with growth charts developed from data collected from children with normal growth or children with CP (Spender et al. 1989; White and Ekvall 1993; Stevenson et al. 2006). Alternatively, they may be used to estimate height using published equations, thus enabling comparison with height-for-age reference charts developed from typically developing children or children with CP (CDC 2000; Stevenson et al. 2006; WHO 2006; Day et al. 2007).